2008
DOI: 10.1111/j.1365-3164.2008.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of commercially available veterinary diets recommended for dogs with atopic dermatitis

Abstract: The classical treatments for dogs with atopic dermatitis have traditionally been oral antipruritic drugs, allergen-specific immunotherapy and topical therapy. Fifty dogs with atopic dermatitis were included in this multicentred, double-blinded, randomized study to compare clinical response to an 8-week period of feeding one of three commercial veterinary foods marketed for dogs with atopic dermatitis (diets A-C) or a widely distributed supermarket food (diet D). Atopic dermatitis was diagnosed using Willemse's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Of the RCTs that tested the evolution of skin lesions over time, the validated third version of the CADESI score was used in 10 studies, 21–24,26,27,29,30,34,35 while five trials employed the second version of this scale, which had limited validation 25,31,33,36,37 . Four trials employed unvalidated scales modified from the first, second or third versions of the CADESI – the so called ‘modified CADESI’ or ‘mCADESI’– having changed the type of lesions, the body sites and/or the severity rating used (A. Puigdemont, personal communication 2012) 28,38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the RCTs that tested the evolution of skin lesions over time, the validated third version of the CADESI score was used in 10 studies, 21–24,26,27,29,30,34,35 while five trials employed the second version of this scale, which had limited validation 25,31,33,36,37 . Four trials employed unvalidated scales modified from the first, second or third versions of the CADESI – the so called ‘modified CADESI’ or ‘mCADESI’– having changed the type of lesions, the body sites and/or the severity rating used (A. Puigdemont, personal communication 2012) 28,38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…A more recent, randomised, double‐blind trial found that a diet high in n3 (480 mg MJ −1 EPA) and n6 (50 mg MJ −1 g‐linolenic acid [GLA]) EFAs significantly improved erythema and pruritus in atopic dogs compared to their usual diets 9 . Additionally, feeding a n3 EFA enriched, n6 EFA controlled diet for eight weeks was recently reported to result in superior improvement of pruritus and other signs in dogs with atopic dermatitis, compared with two other veterinary diets and one non‐veterinary diet 10 …”
Section: Introductionmentioning
confidence: 99%
“…97 A group of 50 dogs with atopic dermatitis were randomly assigned to one of the three therapeutic foods or to the control diet, a commercial adult maintenance food. 97 A group of 50 dogs with atopic dermatitis were randomly assigned to one of the three therapeutic foods or to the control diet, a commercial adult maintenance food.…”
Section: Diet Modificationmentioning
confidence: 99%
“…97 The omega-6 fatty acid content should meet the EFA requirements of dogs and cats, but it should not exceed 4% of the metabolizable energy (ME) calories. The easiest and most effective way to modulate this ratio is by incorporating it directly into the pet's normal diet.…”
Section: Recommended Doses and Ratiosmentioning
confidence: 99%